1990
DOI: 10.1111/j.1523-536x.1990.tb00004.x
|View full text |Cite
|
Sign up to set email alerts
|

Expectations, Experiences, and Psychological Outcomes of Childbirth: A Prospective Study of 825 Women

Abstract: A prospective study of 825 women booked for delivery in six hospitals in southeastern England was conducted to determine their expectations of childbirth. Women completed three questionnaires, two before the birth and one six weeks after. Questions covered both objective and subjective aspects of birth, and gave particular attention to control, its importance and its relevance to psychological outcomes. Four different indices of psychological outcome were considered: fulfillment, satisfaction, emotional well-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
306
6
14

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 424 publications
(341 citation statements)
references
References 18 publications
15
306
6
14
Order By: Relevance
“…As with previous studies (Green 1990, Gibbons and Thomson 2001, Dahlen et al 2010, women within the FGIs said control was an important issue for them.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…As with previous studies (Green 1990, Gibbons and Thomson 2001, Dahlen et al 2010, women within the FGIs said control was an important issue for them.…”
Section: Discussionsupporting
confidence: 68%
“…Unlike Green et al (1990) who found that having high expectations did not lead to feelings of failure, these women felt disappointed that their expectations had not been met, particularly in relation to interventions. A few women had negative childbirth experiences which affected them greatly, in common with many others across the world (Fenwick et al 2005, Olde et al 2006.…”
Section: Discussioncontrasting
confidence: 56%
“…Methodologies were variously described as qualitative (n=4) (Berg et al, 1996;Brown et al, 2009;Dahlen et al, 2010;Walker et al, 1995), using a phenomenological (n=1) (Berg et al, 1996) or Grounded Theory approach (n=3) (Brown et al, 2009;Dahlen et al, 2010;Walker et al, 1995). Two authors utilised quantitative methods (Green et al, 1990;Tumblin & Simkin, 2001). …”
Section: Methodsmentioning
confidence: 99%
“…The literature review highlights that most women value making informed choices and feeling in control (Dahlen et al, 2010;Green et al, 1990;Tumblin & Simkin, 2001). …”
Section: Having Choice and Feeling In Controlmentioning
confidence: 99%
See 1 more Smart Citation